The relationship between internet addiction with eating disorders and musculoskeletal health among university students. - Güneş, Musa; Demirer, Büşra; Şimşek, Ayşe (Journal of Public Health: From Theory to Practice (2198-1833), 2023)
Aim: This study aimed to examine the relationship between internet addiction (IA) with eating disorders and musculoskeletal health problems among university students. Subject and methods: This study was cross-sectional. A total of 581 students (female 459; male 122) were included in the study. Data were collected through an online survey system. The questionnaire form included some socio-demographic information, Young Internet Addiction Test (YIAT), Eating Attitude Test-26 Scale (EAT-26), and Musculoskeletal System Health Questionnaire Scale (MSK-HQ). The data were evaluated with IBM SPSS 25 statistical package program and the GraphPad program. Results: The prevalence of IA of the students participating in the study (mean age 21.24±2.03 years) is 8.4%. It was determined that individuals with IA had statistically significantly more back pain during their internet use compared to individuals who did not (p < 0.05). In addition, it was determined that individuals with IA had a higher risk of eating disorders and as the EAT-26 score increased, the risk of IA increased 1.02 times (OR 1.022; CI 1.001–1.044; p = 0.044). As the MSK-HQ score increases, the probability of being internet addicted also decreases (OR 0.747; CI 0.565–0.987; p = 0.040). Conclusion: This study shows that IA is associated with eating disorders and deterioration in musculoskeletal health problems among university students.